(untitled) (Eurasian Journal of Ecology, 2021)
Data reflecting the current state of Turanga forests in the South-East of Kazakhstan (within the Almaty region) is presented based on the analysis of forest management (as of 01.01.2020) and field surveys by authors in the period 2015-2020. It was found that stunted, understocked stands, which are mainly mature and over-mature in terms of age composition dominate. By the species composition of the stand is prevailed by pure plantings or with a slight admixture of Elaeagnus oxycarpa. Natural regeneration in the form of creeping-rooted specimens was observed only in some small areas, which characterizes the plantings as unstable. Rare, relict and endemic species of trees and shrubs are noted in the composition of the flora of the Turanga forests, their phytocoenotic indexes and practical significance are evaluated. Turanga woodlands need special protection, because these forests have a great environment-forming, soil-fixing, and reclamation value, i.e., they generally stabilize the ecological situation in the floodplains of rivers in arid regions. The main factors of anthropogenic impact on the Turanga forests of the region are shown: changes of the hydrological regime in the Ili River valley, recreation (increasing the road and path network, trampling the soil, setting up campfires), as well as grazing. Proposals are made to improve the protection of these relict forests and an analysis of ways to preserve individual floral elements based on clonal micropropagation methods is given. Key words: Populus pruinosa, Populus diversifolia, bonitet, age-class composition, endemic, relict, abundance, plant community.